Hypothyroidism in children with Hb E/β-thalassemia compared between those who received regular transfusion and those who underwent hematopoietic stem cell transplantation. (2nd January 2023) - Sriwichakorn, Charotorn; Nakavachara, Pairunyar; Jitpirasakun, Sansanee; Pooliam, Julaporn; Sanpakit, Kleebsabai
Abstract: The studies of hypothyroidism in children with transfusion-dependent hemoglobin E/β-thalassemia (TDT), especially in those who underwent hematopoietic stem cell transplantation (HSCT) are limited. We performed a longitudinal retrospective analysis of thyroid function test (TFT) results among TDT patients aged <25 years who received regular transfusion compared to those who underwent HSCT in Faculty of Medicine Siriraj hospital, Thailand during October 2003 to March 2019. Fifty patients (23 TDT, 27 HSCT) were included. The mean age at the last follow-up was 20.1 ± 2.8 vs. 14.5 ± 4.61 years, respectively. The median age at HSCT was 6 (range: 1.9–13.7) years. The prevalence of hypothyroidism among TDT and post-HSCT was 47.8% and 52.2%, respectively. No study patients showed symptoms or signs of hypothyroidism. Subclinical hypothyroidism was the most common type (63.6% of TDT, and 100% of post-HSCT). We found persistent hypothyroidism in 30.4% of TDT, and in 22.2% of post-HSCT. Thyroxine was given in 1 TDT patient with overt hypothyroidism, and in 3 of 6 post-HSCT patients with persistent subclinical hypothyroidism. The ex-thalassemia patients who underwent HSCT after the age of 10 years had a significantly higher risk of post-HSCT hypothyroidism compared to those who underwent HSCT at the age ≤10 years (hazard ratio: 12.01, 95% confidence interval: 1.65–87.41; p = 0.014). In conclusion, hypothyroidism was found to be common in both TDT and post-HSCT patients. Subclinical hypothyroidism without symptoms and signs was the most common type, and was diagnosed only by TFT screening. Long-term regular surveillance of TFT should be performed in both groups of patients.